EIB Group activities in EU cohesion regions in 2021 A bigger, bolder and more focused approach to cohesion - European Investment Bank (European Investment Bank, 2022)
As part of the EIB Group's bigger, bolder and more focused approach to cohesion, this report, the first in a new series, presents the EIB Group's activities in EU cohesion regions in 2021. The results are presented in terms of policy objectives, activity sectors, countries, contribution to the United Nations' Sustainable Development Goals (SDGs) and sector-specific project results. It features a number of case studies and also takes a look at the economic and social challenges facing cohesion regions and the macroeconomic impact of the EIB Group's support for this fundamental EU policy priority.